Health and Well-Being in Late Life: Gender Differences Worldwide - Carmel, Sara (Frontiers in Medicine, 2019)
Maintaining health and quality of life and decreasing the number of years lived with disabilities in old age are among the main challenges of ageing societies worldwide. This paper aims to present current worldwide health-related gender inequalities throughout life, and especially in late life, as well as gender gaps in social and personal resources which affect health, functioning and well-being. This paper also addresses the question of whether gender gaps at younger ages tend to narrow in late life, due to the many biological and social changes that occur in old age. Based on international data regarding these gender gaps and the trends of change in personal resources and health-related lifestyles in the more and less developed nations, conclusions regarding future changes in gender gaps are presented, along with practical implications for future improvements in women's health and well-being.